Daily course of the soil temperature in summer in chosen ecosystems of Słowiński National Park, northern Poland - Bednorz, Ewa; Kolendowicz, Leszek (Quaestiones Geographicae, 2010)
Patterns of the daily changes of the soil temperature in summer at three different ecosystems within the Słowiński National Park were analyzed. Strong correlation between the solar radiation and the soil temperature was found, particularly for the bare sandy surfaces, while the plant and humus cover hampers the solar energy flux to the soil. In the same way, correlations between the temperature of soil surface and the air temperature were computed. Finally, logarithmic models for the relationship between the global solar radiation and the soil surface temperature and between the soil surface temperature and the air temperature were constructed.